The making of the modern Philippines pieces of a jigsaw state - Bowring, Philip (London Bloomsbury Academic, 2022)
"With a fractured geography and complex identity, the Philippines is an eclectic and unique mix of culture, environment, people and politics. Known mostly for natural disasters, migrant labour and dictatorial presidents, in this book Philip Bowring shows how it is much, much more. Deftly navigating the history of this populous island republic, "The Making of the Modern Philippines" traces its history to define and explain its position in the modern world. Looking past the headlines of volcanoes, earthquakes and violence, it asks why has the Filipino economy lagged behind its neighbours, explores the importance of its location in geopolitics, and investigates how its deep-rooted Catholicism clashes with the Islamic consciousness of the region in which it sits. Taking the history of the Philippines from its pre-colonial era, through its Spanish and American occupations and up to the modern day, it unravels the complex politics, culture, peoples and economy of this rich and unique nation. Engaging with challenges the Filipino people face today such as federalism, revolution, Mindanao, the diaspora, capitalism and relations with China, it rediscovers the struggles, culture and history of its past to understand the present"
Includes bibliographic references and index.
Keywords: Philippines -- History; Philippines -- Politics and government; Philippines -- Economic conditions